Introduction of π‑Complexation into Porous Aromatic Framework for Highly Selective Adsorption of Ethylene over Ethane - Li, Baiyan; Zhang, Yiming; Krishna, Rajamani; Yao, Kexin; Han, Yu; Wu, Zili; Ma, Dingxuan; Shi, Zhan; Pham, Tony; Space, Brian; Liu, Jian; Thallapally, Praveen K; et al. (Journal of the American Chemical Society, 2014)
In this work, we demonstrate for the first time the introduction of π-complexation into a porous aromatic framework (PAF), affording significant increase in ethylene uptake capacity, as illustrated in the context of Ag(I) ion functionalized PAF-1, PAF-1-SO3Ag. IAST calculations using single-component-isotherm data and an equimolar ethylene/ethane ratio at 296 K reveal that PAF-1-SO3Ag shows exceptionally high ethylene/ethane adsorption selectivity (S ads: 27 to 125), far surpassing benchmark zeolite and any other MOF reported in literature. The formation of π-complexation between ethylene molecules and Ag(I) ions in PAF-1-SO3Ag has been evidenced by the high isosteric heats of adsorption of C2H4 and also proved by in situ IR spectroscopy studies. Transient breakthrough experiments, supported by simulations, indicate the feasibility of PAF-1-SO3Ag for producing 99.95%+ pure C2H4 in a Pressure Swing Adsorption operation. Our work herein thus suggests a new perspective to functionalizing PAFs and other types of advanced porous materials for highly selective adsorption of ethylene over ethane.